\(\left(a+b\right)^2=5\)
\(a^2+2ab+b^2=5\)
\(a^2+b^2+2\cdot1=5\)
\(a^2+b^2+2=5\)
\(a^2+b^2=3\)
\(\left(a-b\right)^2\)
\(=a^2-2ab+b^2\)
\(=a^2+b^2-2ab\)
\(=3-2\cdot1\)
\(=3-2=1\)
( a + b )2 = 5
⇔ a2 + 2ab + b2 = 5
⇔ a2 - 2ab + b2 + 4ab = 5
⇔ ( a - b )2 + 4ab = 5
⇔ ( a - b )2 + 4.1 = 5 ( gt ab = 1 )
⇔ ( a - b )2 + 4 = 5
⇔ ( a - b )2 = 1
Ta có : (a + b)2 = 5
=> a2 + b2 + 2ab = 5
=> a2 + b2 = 4
Lại có (a - b)2 = a2 - 2ab + b2 = 4 - 2.1 = 2
Vậy (a - b)2 = 2
Có\(\left(a+b\right)^2=5\Leftrightarrow a^2+2ab+b^2=5\)
Thay ab=1
\(\Leftrightarrow a^2+2+b^2=5\Leftrightarrow a^2+b^2=3\)(1)
Có\(\left(a-b\right)^2\Leftrightarrow a^2-2ab+b^2\)
Thay ab=1
\(\Leftrightarrow a^2-2+b^2\)
Thay (1) vào có
\(\Leftrightarrow\left(a^2+b^2\right)-2\Leftrightarrow3-2=1\)
Vậy giá trị của \(\left(a-b\right)^2=1\)
Bài giải
\(\left(a+b\right)^2=a^2+2ab+b^2=a^2+b^2+2=5\)
\(\Rightarrow\text{ }a^2+b^2=3\)
\(\Rightarrow\text{ }\left(a-b\right)^2=a^2-2ab+b^2=a^2+b^2-2=3-2=1\)
Ta có: (a + b)2 = 5
<=> a2 + 2ab + b2 = 5
<=> a2 - 2ab + b2 + 4ab = 5
<=> (a - b)2 + 4 = 5 (do ab = 1)
<=> (a - b)2 = 1
Vậy (a - b)2 =1
Linz
Bài làm :
Ta có :
( a + b )2 = 5
<=> a2 + 2ab + b2 = 5
<=>a2 - 2ab + b2 + 4ab = 5
<=> ( a - b )2 + 4ab = 5
<=> ( a - b )2 + 4.1 = 5
<=> ( a - b )2 + 4 = 5
<=> ( a - b )2 = 1
Vậy ( a - b )2 = 1